Experimental investigation of end milling operation on Al2024. (2017) - B.Sahare, Shilpa; Untawale, Sachin P.; Chaudhari, Sharad S.; Shrivastav, Rakesh L.; Kamble, Prashant D.
Abstract: This research paper aims to find out the optimum cutting condition for end milling operation on material Al2024. In this research project an on-going comparative study will be made for surface roughness, metal removal rate and cutting forces by varying cutting parameters such as cutting speed, feed per tooth and depth of cut under various cutting condition. Experimentation performed and results compared with dry, wet and lubrication at various flow rate. A mathematical model will also be developed to determine the surface roughness, cutting forces and metal removal rate in terms of the three independent variables: cutting speed, feed rate, and depth of cut. The results obtained with the application of optimal lubricant technique will significantly helps to obtain better performance in compare to dry condition. The cutting fluid plays significant role toward machining cost, health issues and also helps to reduce environmental pollution.